Transmission features of frequency-selective components in the far infrared determined by terahertz time-domain spectroscopy - Winnewisser, Carsten; Lewen, Frank; Weinzierl, Jochen; Helm, Hans (Applied Optics, 1999)
The transmission features in the far infrared region of dichroic high-pass filters and a cross-shaped bandpass filters are studied using an electro-optic sampling terahertz time-domain spectrometer. The frequency-selective components (FSC) transmission experiments show good agreement with the transmission theories, showing that they can be applied for a priori filter design.